2011
DOI: 10.1186/1746-1596-6-89
|View full text |Cite
|
Sign up to set email alerts
|

Maspin and MCM2 immunoprofiling in salivary gland carcinomas

Abstract: BackgroundThe pathogenesis of salivary gland carcinomas is very complex and prognostic markers are difficult to find in these carcinomas of which the different subtypes have varying malignant potential. The study was conducted to examine the cellular distribution of maspin and MCM2 in salivary gland carcinomas and their value to predict lymph node metastasis.Materials and methodsFifty three paraffin blocks of different lesions (15 muco-epidermoid carcinoma, 14 adenoid cystic carcinoma, 3 epi-myoepithelial carc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
14
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 42 publications
6
14
1
Order By: Relevance
“…In accordance with previous studies (20,21), the results of this study showed inverse significant association between maspin expression and histologic grade. No significant correlation was found between maspin expression and lymph node metastasis, which was similar to Ghazy et al's study (22), but in contrast to the findings of Schwartz et al (23). This discrepancy may be attributed to the method of expression evaluation and the number of samples .Of note, we encountered limitation in sample collection due to incomplete data in patients' record and lack of paraffin blocks.…”
Section: Discussioncontrasting
confidence: 54%
“…In accordance with previous studies (20,21), the results of this study showed inverse significant association between maspin expression and histologic grade. No significant correlation was found between maspin expression and lymph node metastasis, which was similar to Ghazy et al's study (22), but in contrast to the findings of Schwartz et al (23). This discrepancy may be attributed to the method of expression evaluation and the number of samples .Of note, we encountered limitation in sample collection due to incomplete data in patients' record and lack of paraffin blocks.…”
Section: Discussioncontrasting
confidence: 54%
“…Cho et al [46] suggested that high PCNA (proliferating cell nuclear antigen) expression is significantly associated with shorter disease-free and overall survival of patients with AdCCs. Minichromosome maintenance (MCM) protein expression has been found to be a novel marker for proliferating tumor cells and is diagnostically useful for the differential diagnosis of benign and malignant salivary gland tumors [47]. The expression of the argyrophylic nucleolar organizer region (AgNOR) associated proteins were also an independent prognostic factor in these tumors [48].…”
Section: Cell Cycle-based Proliferation Markersmentioning
confidence: 99%
“…Salivary gland tumours, including PLGA and ACC, stained positively for both maspin and MCM2 to a variably degree, but ACC showed a higher proliferation profile versus PLGA. There was no significant correlation between maspin and MCM2 expression and regional metastatic disease [48]. …”
Section: Maspin and Mini-chromosome Maintenance Protein (Mcm2)mentioning
confidence: 79%
“…Maspin is a mammary serine protease inhibitor, that functions to prevent apoptosis and decrease cell invasion, and may have a role in preventing angiogenesis [48]. MCM2's are mini chromosome maintenance proteins, which are paramount for DNA replication and therefore, have use as markers for cell proliferation [48].…”
Section: Maspin and Mini-chromosome Maintenance Protein (Mcm2)mentioning
confidence: 99%
See 1 more Smart Citation